Chitosan modifies glycemic levels in people with metabolic syndrome and related disorders: meta-analysis with trial sequential analysis - Guo, Wenfang; Yi, Letai; Zhou, Baochang; Li, Minhui (Nutrition journal, 2020)
Background Chitosan supplementation has been shown to modulate glycemic levels; however, studies have reported conflicting results. The present meta-analysis with trial sequential analysis was conducted to verify the overall influence of chitosan on glycemic levels in patients with metabolic syndrome. Methods The PubMed, Cochrane library, and EMBASE databases were systematically searched for randomized controlled studies of chitosan intake and glycemic levels. Results A total of ten clinical trials including 1473 subjects were included in this meta-analysis. Pooled effect sizes were determined by random-effects meta-analysis. Subgroup analysis was performed to analyze the sources of heterogeneity and their influence on the overall results. The results revealed a significant reduction in fasting glucose levels (SMD: − 0.39 mmol/L, 95% CI: − 0.62 to − 0.16) and hemoglobin A1c (HbA1c) levels (SMD: -1.10; 95% CI: − 2.15 to − 0.06) following chitosan supplementation but no effect on insulin levels (SMD: − 0.20 pmol/L, 95% CI: − 0.64 to 0.24). Subgroup analyses further demonstrated significant reductions in fasting glucose levels in subjects administered 1.6–3 g of chitosan per day and in studies longer than 13 weeks. Trial sequential analysis of the pooled results of the hypoglycemic effect demonstrated that the cumulative Z-curve crossed both the conventional boundary and trial sequential monitoring boundary for glucose and HbA1c. Conclusions The glucose level of patients who are diabetic and obese/overweight can be improved by supplementation with chitosan for at least 13 weeks at 1.6–3 g per day. Additional clinical research data are needed to confirm the role of chitosan, particularly in regulating glycosylated hemoglobin and insulin.